A prospective, comparative survey to investigate practitioners' satisfaction with a cohesive, polydensified‐matrix®, hyaluronic acid‐based filler gel with and without lidocaine for the treatment of facial wrinkles. (10th May 2015) - Prager, Welf; Micheels, Patrick
Summary: Background: Lidocaine‐containing dermal fillers may reduce procedural pain compared with lidocaine‐free counterparts. Objectives: To assess practitioners' administration experience with, and the efficacy and safety of, a cohesive, polydensified‐matrix ®, hyaluronic acid‐based filler containing lidocaine vs . its lidocaine‐free counterpart. Methods: The lidocaine‐containing formulation was injected to one side of the face and the lidocaine‐free to the other in 29 females (30–85 years). Administered dose was appropriate to the treatment zone and technique varied according to zone and practitioner preference. Questionnaires assessed practitioners' administration experience, their perception of results, subject satisfaction, and product safety. Results: Practitioners considered the formulations to be similar in terms of ejection force, texture, and placement. The blanching technique was used for 72% of subjects, and its ease was rated as "identical" for both products in 81% of applications and "easier" for the lidocaine‐containing product in 6.9% of applications. Results with both formulations were "identical" for 86% of applications and "similar" for the remainder. In 86% of cases, practitioners would "certainly" consider continuing treatment with the lidocaine‐containing formulation. All subjects were "satisfied" with treatment. Practitioners reported that, compared with the lidocaine‐free product, subject‐assessed pain with the lidocaine‐containing product was "less prominent" for 86% and 79% of participants during and following treatment, respectively. Similarly, mean pain intensity was significantly lower for the lidocaine‐containing preparation ( P = 0.0001). Adverse events were similar for both treatments. Conclusions: The lidocaine‐containing dermal filler significantly reduced pain during and following treatment compared with the same preparation without lidocaine, without impact on administration, aesthetic outcome, or safety.